Potensi Konflik Kekerasan Antar Kelompok Narapidana dalam Lembaga Pemasyrakatan Kelas II A Tangerang - Yuliyanto Yuliyanto (Badan Strategi Kebijakan Hukum, 2012)
The purpose of this study is to determine the potential of violent conflict between groups of inmates, the causal factors of violent conflict between groups of inmates and to describe any treatment efforts and problem solving violent conflicts between groups of inmates in correctional institutions, so that it can be used as an input and advice to the stakeholders in the area of violent conflict resolution and management among the group of prisoners in correctional institutions. This study uses a qualitative approach, with a research strategy that uses and gathers in depth data/information about the phenomenon of violent conflict in correctional institutions. The data and information and research results will illustrate this phenomenon qualitatively along with its mutual relations analysis between the phenomenon and the relevant factors involved. The research also applies literature study and field work as tools and techniques for data collection. Furthermore, the research reveals several points: first, conflicts between inmates in the Penitentiary Class IIA Tangerang are quite common with low level of conflict escalation and involving private matters of the inmates. Such conflicts is mostly caused by small matters such as debt issues, lost of personal belongings (money, toiletries), and misunderstandings-such as attitudes that are considered arrogant or even insulting. Second, the conflict or dispute is likely to be resolved between inmates or involving the leaders and chief of each block. Such a measure was ussually taken to prevent a wider conflict. In addition, if such an issue reaches the officer's room, there shall be a following penalty imposed by the officers. If the problems faced are considered heavy and difficul to reach a common ground, then the prison officers should be involved. The recommendations presented in this study are: first, there is a need for a more comprehensive guidance for people considering some psychological effects they burden during their sentences. Secondly, in guiding the inmates, there are several measures that can be taken for instance by giving them training on skills they could use after serving their sentences in prison. Third, coaching and skills training need to be implemented with the involvement of other agencies outside the correctional institution, whether public or private agency, or any social institutions that intend and are concerned about the problems faced by the inmates in correctional institutions. Fourth, the leadership in correctional institutions requires a leader who is capable in nurturing the attitude of the inmates and he/she should have adequate managerial skills in managing prisons in order to be a good organization.